2023
DOI: 10.1002/adfm.202307402
|View full text |Cite
|
Sign up to set email alerts
|

A Facile Strategy to Fabricate Tough and Adhesive Elastomers by In Situ Formation of Coordination Complexes as Physical Crosslinks

Jia Yu Hu,
Dejin Jiao,
Xing Peng Hao
et al.

Abstract: Coordination bonds with a dynamic nature and wide‐spectrum bond energy have gained great popularity in use for fabricating tough soft materials. However, most existing coordination‐based elastomers are prepared through complicated procedures, usually involving elaborate synthesis of ligand‐containing monomers or polymers, ion diffusion to form coordination complexes, and removal of organic solvent during the synthesis, which are neither easy operation nor environmentally friendly. Here, a facile and effective … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(3 citation statements)
references
References 65 publications
0
3
0
Order By: Relevance
“…The two elastomer films with different colors were first cut into two pieces. Then, the dark green (Cu/Dy mole ratio of 2:1) and light green (Cu/Dy mole ratio of 1:2) elastomer films were spliced together and placed in an oven at 80 °C for 1 h. Similar to other metallogels and metalloelastomers, the two pieces of elastomer films were reassembled. The photo images clearly showed the remerging of surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…The two elastomer films with different colors were first cut into two pieces. Then, the dark green (Cu/Dy mole ratio of 2:1) and light green (Cu/Dy mole ratio of 1:2) elastomer films were spliced together and placed in an oven at 80 °C for 1 h. Similar to other metallogels and metalloelastomers, the two pieces of elastomer films were reassembled. The photo images clearly showed the remerging of surfaces.…”
Section: Resultsmentioning
confidence: 99%
“…This indicated that the number of Zr 4+ crosslinking in the S-PAZr was reduced after the salting-out treatment, whereas the Zr 4+ coordination state was not significantly changed (Fig. 2c) 39 . The crystalline domain evolution of the S-PAZr was discussed by X-ray diffraction (XRD) analysis.…”
Section: Structural Evolution and Toughening Mechanism Of The S-pazr ...mentioning
confidence: 87%
“…Benefiting from the elaborated ionic crosslinking and crystalline domains, the S-PAZr hydrogel fiber could synergistically dissipate energy through ionic decoordination and crystalline domain unfolding during stretching (Supplementary Figs. 4, 5) 39,[49][50][51] . As a result, the S-PAZr hydrogel fiber exhibited high mechanical properties, such as tensile stress of 24.43 ± 2.11 MPa, tensile strain of 844.44 ± 107.21%, elastic modulus of 36.81 ± 1.58 MPa, and toughness of 162.25 ± 21.99 MJ/m 3 (Fig.…”
Section: Structural Evolution and Toughening Mechanism Of The S-pazr ...mentioning
confidence: 99%